Die debatteerbare kerkregtelike relevansie tussen 1618, 1816 en 1951 in verhouding tot die Kerkorde van die Nederduitsch Hervormde Kerk van Afrika - Wyk, Barry J. van (HTS teologiese studies, 2020)
The debatable church orderly relevance between 1618, 1816 and 1951 in relation to the church order of the Netherdutch Reformed Church of Africa: The above-mentioned dates from the past, although distant from each other, are linked to each other and influential in the church law debate, even in recent times. The intention of this paper is to link the dates as well as the events associated with the mentioned dates from the past with the church order of the Netherdutch Reformed Church of Africa which was determined during the church’s 71st synod meeting during 2016. Churches in South Africa originated from the 16th century Reformation should accommodate each other even with some different viewpoints especially in connection with church law as formulated and practised in different churches.Contribution: The contribution of this paper is to point out that the relation between the mentioned dates indicate important milestones in the church orderly past, in the Netherlands and in South Africa and should be treated with caution, especially in reference to the church order of the Netherdutch Reformed Church of Africa.